2023
DOI: 10.3788/pi.2023.r09
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive optical elements 75 years on: from micro-optics to metasurfaces

Qiang Zhang,
Zehao He,
Zhenwei Xie
et al.

Abstract: Diffractive optical elements (DOEs) are intricately designed devices with the purpose of manipulating light fields by precisely modifying their wavefronts. The concept of DOEs has its origins dating back to 1948 when D. Gabor first introduced holography. Subsequently, researchers introduced binary optical elements (BOEs), including computer-generated holograms (CGHs), as a distinct category within the realm of DOEs. This was the first revolution in optical devices. The next major breakthrough in light field ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 427 publications
0
0
0
Order By: Relevance
“…Figure 19 illustrates further advanced applications of dielectric metasurfaces. More detailed reviews about the applications of metasurfaces across various domains can be found in previous literature [326][327][328][329] . This miniaturization advantage of meta-devices has led to notable advancements in various applications, including aerial [330] , terrestrial [331] , and underwater [318,332] environments, particularly benefiting modern consumer optoelectronic devices such as augmented reality (AR), virtual reality (VR), and unmanned aerial vehicles [333] , among others.…”
Section: Perspective and Outlookmentioning
confidence: 99%
“…Figure 19 illustrates further advanced applications of dielectric metasurfaces. More detailed reviews about the applications of metasurfaces across various domains can be found in previous literature [326][327][328][329] . This miniaturization advantage of meta-devices has led to notable advancements in various applications, including aerial [330] , terrestrial [331] , and underwater [318,332] environments, particularly benefiting modern consumer optoelectronic devices such as augmented reality (AR), virtual reality (VR), and unmanned aerial vehicles [333] , among others.…”
Section: Perspective and Outlookmentioning
confidence: 99%